Introduction of “Internet of Things” its Application and Challenges (International Journal of Engineering and Computer Science, 2015)
In recent years, the term “Internet of Things” has spread rapidly we’re entering a new era of computing technology that many are calling the Internet of Things (IoT). Machine to machine, machine to infrastructure, machine to environment, the Internet of Everything, the Internet of Intelligent Things, intelligent systems call it what you want, but it’s happening, and its potential is huge. We see the IoT as billions of smart, connected “things” (a sort of “universal global neural network” in the cloud) that will encompass every aspect of our lives, and its foundation is the intelligence that embedded processing provides. The IoT is comprised of smart machines interacting and communicating with other machines, objects, environments and infrastructures. As a result, huge volumes of data are being generated, and that data is being processed into useful actions that can “command and control” things to make our lives much easier and saferand to reduce our impact on the environment. The creativity of this new era is boundless, with amazing potential to improve our lives. Now consider that IoT represents the next evolution of the Internet, taking a huge leap in its ability to gather, analyze, and distribute data that we can turn into information, knowledge, and, ultimately, wisdom. In this context, IoT becomes immensely important.